Pengembangan Media Pembelajaran Fisika Berbasis Android Pada Materi Pesawat Sederhana Menggunakan Adobe Animate - Restiani, Dian Ayu; Wahyudi, Muh (Alpatih Harapan Semesta, 2024)
The background of this research is that teachers still have difficulty using available learning media and many physics learning tools/media are not suitable for use. This study aims to produce physics learning media with Android-based simple aircraft material using Adobe Animate applications that have valid criteria. The research instrument used is a validation questionnaire for material experts, media experts, and student responses using small group trials and large group trials at grade VIII junior high schools. This research was conducted at SMP Negeri 4 Satap Liukang Tangaya. This research is a Research and Developmend (R&D) research with the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The results of this study are Android-based learning media with material expert validation obtained a percentage value of 92.4% with a category very feasible to use, while the assessment of media experts obtained a percentage value of 93.33% with a very feasible category. Small group and large group trials on junior high school students in class VIII were obtained a percentage value of 93.5% and 93.5% which were categorised as very valid or very good. In conclusion, android-based physics learning media on simple aircraft material using adobe animate grade VIII SMP is effective and feasible to use as a junior high school learning media.